2014
DOI: 10.1007/s00125-014-3459-6
|View full text |Cite
|
Sign up to set email alerts
|

SORBS1 gene, a new candidate for diabetic nephropathy: results from a multi-stage genome-wide association study in patients with type 1 diabetes

Abstract: Background The genetic determinants of diabetic nephropathy remain poorly understood. We aimed to identify novel susceptibility genes for diabetic nephropathy. Patients and methods We performed a genome-wide association study using 1000 Genomes-based imputation in type 1 diabetic patients comparing diabetic nephropathy cases with proteinuria with or without renal failure to controls with diabetes for more than 15 years and no evidence of renal disease. Results None of the SNPs tested in a discovery cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 11 publications
0
33
0
Order By: Relevance
“…Also, the various GWAS for DR and DKD have examined different case definitions including PDR, NPDR, DME, proteinuria, AER, and ESRD. In some studies, participants with NPDR and microproteinuria were classified as controls [43][44][45]87], whereas in other studies they were considered cases [46, 61,82,89].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the various GWAS for DR and DKD have examined different case definitions including PDR, NPDR, DME, proteinuria, AER, and ESRD. In some studies, participants with NPDR and microproteinuria were classified as controls [43][44][45]87], whereas in other studies they were considered cases [46, 61,82,89].…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Germain et al performed a GWAS comparing T1D cases with proteinuria (with or without renal failure) with control patients who have had diabetes for more than 15 years and no evidence of renal disease [89]. No SNPs tested in a discovery cohort consisting of 683 cases and 779 controls reached genome-wide statistical significance.…”
Section: Genome Wide Association Studiesmentioning
confidence: 99%
“…Furthermore, natural history studies (mostly in subjects with type1 DM) indicate that the degree of hyperglycemia correlates with DKD incidence. Based on these observations, investigators have tried to control glycemia almost to the degree of non-diabetic levels in the ACCORD, ADVANCE, and VA-DT clinical trials [24]. Surprisingly, these studies failed to show lower mortality and complication rates.…”
Section: Great Emphasis But Limited Success With Predisposition Dkd mentioning
confidence: 99%
“…Interestingly, a transethnic meta-analysis revealed that the MYO16/IRS2 locus would be associated with susceptibility to both type 1 and 2 diabetic nephropathies (29), and a SCAF8 variant was consistently associated with type 2 diabetic nephropathy across populations of different ancestry (30) (see dark gray in Figure 2). In addition, GWAS carried out in European populations highlighted several associations with type 1 diabetes-associated ESRD (31,32), and other studies revealed candidates for both type 1-and type 2-associated ESRD (26,(33)(34)(35)(36)(37). However, a subsequent comprehensive, large, meta-GWAS effort was unable to identify clear loci consistently associated with diabetic nephropathy and many of the previous identified candidate signals were not validated (28).…”
Section: Specific Etiologies Diabetic Nephropathymentioning
confidence: 99%